KOREOGRAFI TARI TANDUAK PADA SANGGAR SEKAPUR SIRIH DI NAGARI LUBUK TAROK KABUPATEN SIJUNJUNG - Yesa, Istifadilla; Mansyur, Herlinda (Universitas Negeri Padang, 2026)
This study aims to describe and analyze the choreography of the Tanduak Dance at the Sekapur Sirih Studio in Lubuk Tarok Village, Sijunjung Regency. Tanduak Dance is a traditional dance that has historical, symbolic, and cultural identity values ​​​​of the local community. The study uses a qualitative approach with a descriptive analytical method. Data was obtained through observation, interviews, literature studies, and documentation. The results of the study indicate that the choreography of the Tanduak Dance consists of aspects of form and content. Form aspects include movement, floor design, upper design, group composition, dancers, costumes, dancers, costumes, properties, and musical accompaniment. The main movement variety consists of Gerak Sambah, Langkah Ampek, Langkah Sepai, and Langkah Kicuah which are dominated by meaningful movements with silat nuances. The floor pattern utilizes straight, curved, and oblique lines with a group formation of seven dancers. Content aspects include ideas about courage and symbolic buffalo fighting, as well as heroic and dynamic nuances. This dance represents the values ​​​​of courage, preparedness, and cultural identity of the Lubuk Tarok Village community.